Implementasi Satuan Pendidikan Aman Bencana terhadap Kesiapsiagaan Bencana Gempa Bumi pada Siswa - Yulianty Tae, Patricia Mega Sri; Indarwati, Retno; Armini, Ni Ketut Alit (Journal of Telenursing (JOTING), 2024)
This research aims to determine whether increased knowledge and changes in disaster preparedness behavior can be formed properly through a comprehensive education process that has a long and sustainable impact. The effectiveness of the learning approach through the disaster curriculum method in schools can optimize educational outcomes from the disaster preparedness curriculum. The method used in this research is cross sectional with a total percentage of 67%, then Quasi-Experiment 27% and Experiment 6%. The results of the research show that the influence of the Disaster Safe Education Unit Program on Disaster Preparedness Education can be seen from the results of the analysis of studies in Indonesia showing that Disaster safety education unit education significantly increases students' knowledge, attitudes and actions in dealing with earthquakes and that this program can certainly increase students' knowledge, metacognitive awareness, safety behavior and general well-being regarding earthquakes. The overall conclusion of this research is that the Disaster Safe Education Unit program has had a significant positive impact on students' preparedness for earthquakes. Keywords: Earthquake Disaster Disaster Preparedness, Students, Disaster Safe Education